Eco-friendly precision turning of superalloy Inconel 718 using MQL based vegetable oils: Tool wear and surface integrity evaluation. (January 2022) - Saleem, Muhammad Qaiser; Mehmood, Abrar
Abstract: This work reports on the performance of eco-friendly spray-based approach employing vegetable oils to precision machine nickel based superalloy Inconel 718. Taguchi L9 (3 3 ) orthogonal array was used to evaluate two vegetable oils namely sunflower and castor oil for turning operation and their performance was compared with dry machining mode. Three levels of cutting speed (30, 50, 70 m/min.), feed rate (0.168, 0.281, 0.393 mm/rev.) and air pressure (2, 3.5, 5 bar) were used while keeping constant depth of cut (1) mm and spray standoff settings (50 mm). Tool wear, surface roughness and machined surface integrity were taken as response parameters. Tool wear analysis was further supplemented with scanning electron microscopy (SEM). The effects of the input variables on response parameters were quantified by analysis of variance (ANOVA). It was found that feed rate is the most contributing factor for surface roughness with a contribution of 95.71%, 97.86% and 93.19% for MQLSO, MQLCO and dry machining conditions respectively. As for the tool wear, cutting speed is the most contributing factor with a contribution of 76.55%, 80.87% and 69% for MQLSO, MQLCO and dry machining conditions respectively. Minimum tool wear was obtained with sunflower oil with lowest feed rate (0.168 mm/rev.) and cutting speed (30 m/min.) combination. Further insight on worst and least tool wear conditions via SEM images indicate grooving, incidences of adhered material and attrition/chipping to be observable for dry machining condition. On the other hand, lesser incidences of adhered chips and uniform wear which extended up-to the tool nose was observed for least tool wear condition obtained with MQLSO indicting its effectiveness. The minimum values for tool wear (116 μm) and surface roughness (0.43 μm) as obtained with MQLSO, were 26% and 52.09% better (respectively) when compared to the dry machining at same conditions. In the context of surface integrity, a strain hardened layer extending up to the depth of 270 μm was observed at optimum machining parameters. Approximately, 16% higher hardness value was observed closer to the machined surface, than that of bulk material.